Interval colourings of some regular graphs - Rafael R. Kamalian; Petrosyan, Petros (Изд-во НАН РА)
A lower bound is obtained for the greatest possible number of colors in an interval colourings of some regular graphs.
Keywords: Mathematics; Graph theory